Resolution of Pulmonary Inflammation Induced by Carbon Nanotubes and Fullerenes in Mice: Role of Macrophage Polarization - Lim, Chol Seung; Porter, Dale W.; Orandle, Marlene S.; Green, Brett J.; Barnes, Mark A.; Croston, Tara L.; Wolfarth, Michael G.; Battelli, Lori A.; Andrew, Michael E.; Beezhold, Donald H.; Siegel, Paul D.; Ma, Qiang (Frontiers in Immunology, 2020)
Pulmonary exposure to certain engineered nanomaterials (ENMs) causes chronic lesions like fibrosis and cancer in animal models as a result of unresolved inflammation. Resolution of inflammation involves the time-dependent biosynthesis of lipid mediators (LMs)—in particular, specialized pro-resolving mediators (SPMs). To understand how ENM-induced pulmonary inflammation is resolved, we analyzed the inflammatory and pro-resolving responses to fibrogenic multi-walled carbon nanotubes (MWCNTs, Mitsui-7) and low-toxicity fullerenes (fullerene C60, C60F). Pharyngeal aspiration of MWCNTs at 40 µg/mouse or C60F at a dose above 640 µg/mouse elicited pulmonary effects in B6C3F1 mice. Both ENMs stimulated acute inflammation, predominated by neutrophils, in the lung at day 1, which transitioned to histiocytic inflammation by day 7. By day 28, the lesion in MWCNT-exposed mice progressed to fibrotic granulomas, whereas it remained as alveolar histiocytosis in C60F-exposed mice. Flow cytometric profiling of whole lung lavage (WLL) cells revealed that neutrophil recruitment was the greatest at day 1 and declined to 36.6% of that level in MWCNT- and 16.8% in C60F-treated mice by day 7, and to basal levels by day 28, suggesting a rapid initiation phase and an extended resolution phase. Both ENMs induced high levels of proinflammatory leukotriene B4 (LTB4) and prostaglandin E2 (PGE2) with peaks at day 1, and high levels of SPMs resolvin D1 (RvD1) and E1 (RvE1) with peaks at day 7. MWCNTs and C60F induced time-dependent polarization of M1 macrophages with a peak at day 1 and subsequently of M2 macrophages with a peak at day 7 in the lung, accompanied by elevated levels of type 1 or type 2 cytokines, respectively. M1 macrophages exhibited preferential induction of arachidonate 5-lipoxygenase activating protein (ALOX5AP), whereas M2 macrophages had a high level expression of arachidonate 15-lipoxygenase (ALOX15). Polarization of macrophages in vitro differentially induced ALOX5AP in M1 macrophages or ALOX15 in M2 macrophages resulting in increased preferential biosynthesis of proinflammatory LMs or SPMs. MWCNTs increased the M1- or M2-specific production of LMs accordingly. These findings support a mechanism by which persistent ENM-induced neutrophilic inflammation is actively resolved through time-dependent polarization of macrophages and enhanced biosynthesis of specialized LMs via distinct ALOX pathways.